Haushaltsarbeit und affektive Arbeit: über Feminisierung und Kolonialität von Arbeit - Gutiérrez Rodríguez, Encarnacion (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2014)
The central topic of this article is the social devaluation of domestic work, especially focusing on its affective dimension. The question of reproduction as well as the productive character of care-work is constantly neglected in many socioeconomic studies. This counts also for Marxist analyses. Following enquiries in European countries on how domestic work is sensed, how this impacts the people delivering this work, as well as how these feelings linger in spaces and are transferred within relations, the results are interpreted in the context of processes of feminization and the coloniality of labor. Special attention is given to the situation of undocumented migrant domestic workers. As conclusion to these observations some thoughts on formulating domestic workers’ rights along the lines of the politics of affect are elaborated.